Isolation of seawater microplastics from biologically rich samples using an alkaline K2S2O8 method - Gao, Nan; Kong, Xiangfeng; Zhang, Yanmin; Gao, Yang; Zhang, Yuanbiao; Liu, Yan (Frontiers in Marine Science, 2024)
In recent years, microplastics, especially marine microplastic pollution, have received global attention as a new type of environmental problem. The establishment of accurate and efficient methods for the detection of microplastics is the basis for in-depth research on the transport, transformation, fate, and ecotoxicological effects of microplastics in the environment. Microplastics in seawater frequently mix with biological tissues, resulting in challenges when identifying samples. However, commonly used pretreatment protocols for microplastics often suffer from long digestion times, inadequate digestion, and the risk of potentially damaging microplastics. This study compared the digestion efficiencies of five digestion reagents and provided further insights into two advanced oxidation methods involving Fenton’s reagent and an innovative alkaline K2S2O8 protocol based on sulfate and hydroxyl radicals. Using Raman spectroscopy, scanning electron microscopy-energy dispersive spectroscopy (SEM−EDS), and carbonyl index (CI) analyses, the status of microplastics after pretreatment was evaluated. The results revealed that the alkaline K2S2O8 method could enhance the reaction efficiency while reducing the potential for functional group damage during microplastic pretreatment. Moreover, the proposed K2S2O8 method was applied to the pretreatment of field seawater samples, and field microplastics were effectively separated from biologically rich samples. Thus, a digestion protocol based on alkaline K2S2O8 provides an effective way to isolate seawater microplastics from biologically rich samples. This study contributes to the development of efficiently microplastic monitoring and provides valuable insights into access to reliable data for fate and inventory of oceanic microplastics.